Enhancing Program Outcomes and Academic Performance through Problem-Based Learning in an Antennas and Wave Propagation Course - S. V., Devika; Siddapuram, Arvind; Kaur, Rashpinder; P., Kondala Rao (Journal of Engineering Education Transformations, 2025)
Problem-Based Learning (PBL) is increasingly recognized as an effective educational approach in engineering education, helping improve critical thinking and practical skills. In the context of the Antennas and Wave Propagation course for third-year Electronics and Communication Engineering (ECE) students, traditional teaching methods often fall short in engaging students and addressing all program outcomes (POs). This study involved implementing PBL in the Antennas and Wave Propagation course, where students were divided into teams and given a problem statement related to the course. Each team was tasked with developing a solution and creating a prototype. The implementation included several steps: defining the problem, brainstorming, research, solution design, prototype development, and final presentation. Data was collected through predefined rubrics assessing various criteria, such as problem understanding, solution quality, teamwork, and presentation skills. The rubrics were designed to map each activity to specific POs. The collected data was analyzed to compare the target and attained values of each PO to evaluate the effectiveness of PBL. The preliminary results indicate a positive impact of PBL on both student engagement and academic performance. Students demonstrated improved understanding and application of theoretical concepts, as evidenced by the quality of their prototypes and presentations. The analysis shows that the academic performance of the students is improved and attained values for most POs met or exceeded the target values, particularly in areas like problem-solving (PO2), Engineering design (PO3), Conduct Investigations (PO4), Modern tool usage (PO5), Teamwork (PO 9) and Project Management (PO11). Student feedback was overwhelmingly positive, highlighting enhanced learning experiences and increased motivation. This study explores the implementation of PBL to improve academic performance and ensure comprehensive coverage of POs.